The Forgotten Rationale for Policy Reform: The Productivity of Investment Projects - Isham, J.; Kaufmann, D. (Quarterly Journal of Economics, 1999)
Using economic rates of return from World Bank-funded investments, we investigate how country characteristics and policies that influence aggregate performance affect investment productivity. Controlling for other characteristics, countries with undistorted (distorted) macroeconomic, exchange rate, trade, and pricing policies have highly productive (unproductive) investments. No type of project—in tradable or nontradable sectors—can be “insulated” from poor policies, where returns on investments are about ten percentage points lower Productivity increases when policies improve within a country. Projects are also affected, nonlinearly, by the size of the public investment program where policies are undistorted. The results offer new evidence on benefits from policy reform and challenge conventional cost-benefit analysis.